The Influence of Brand Image, Price Perception, and Local Wisdom-Based Promotional on Buyer's Decision - Nopera, Tesi; Putri, Dini Elida; Hasibuan, Anggy Qurnia Raafy (UPI YPTK Journal of Business and Economics, 2024)
This study analyzes the influence of brand image, price perception, and local wisdom-based promotional strategies on the purchasing decisions for Tebo Riski Danang batik in Tebo Regency, Jambi Province. Tebo batik is unique, and Rumah Batik Riski Danang stands out by producing and marketing it, highlighting the region's history and distinctiveness. The research employed a quantitative method with questionnaires distributed to 255 respondents in Tebo Tengah District. The analysis included validity, reliability, correlation, and multiple linear regression. The findings revealed that brand image negatively impacts purchasing decisions, while price perception has a positive influence. However, the promotional strategy does not significantly affect purchasing decisions. Simultaneously, the three variables together significantly influence purchasing decisions. Brand image, price perception, and promotional strategy explain 41.4% of the variation in purchasing decisions, with other factors accounting for the remaining 58.6%. In conclusion, brand image and price perception are crucial in shaping purchasing decisions for Tebo Riski Danang batik, while the promotional strategy has no significant impact.